2017
DOI: 10.1128/genomea.01021-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus velezensis 3A-25B, a Strain with Biocontrol Activity against Fungal and Oomycete Root Plant Phytopathogens, Isolated from Grassland Soil

Abstract: Here, we present the draft genome of Bacillus velezensis 3A-25B, which totaled 4.01 Mb with 36 contigs, 3,948 genes, and a GC content of 46.34%. This strain, which demonstrates biocontrol activity against root rot causal phytopathogens in horticultural crops and friendly interactions in roots of pepper plantlets, was obtained from grassland soil in Zacatecas Province, Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Lim et al [ 73 ] recently reported a B. velezensis strain capable of producing antifungal volatile and agar-diffusible metabolites that inhibited mycelial growth of several plant pathogenic fungi. Similarly, Martínez-Raudales et al [ 74 ] evidenced an antifungal activity of B. velezensis against N. solani , F. oxysporum , Phytophthora capsici , and R. solani , causative agents of chili pepper root rot.…”
Section: Discussionmentioning
confidence: 95%
“…Lim et al [ 73 ] recently reported a B. velezensis strain capable of producing antifungal volatile and agar-diffusible metabolites that inhibited mycelial growth of several plant pathogenic fungi. Similarly, Martínez-Raudales et al [ 74 ] evidenced an antifungal activity of B. velezensis against N. solani , F. oxysporum , Phytophthora capsici , and R. solani , causative agents of chili pepper root rot.…”
Section: Discussionmentioning
confidence: 95%
“…Microbial biocontrol agents have gained increasing attention due to their effectiveness, environmental friendliness, and safety for humans and livestock (Berg, 2009). As an important biocontrol agent, B. velezensis is a relatively novel species, and research on the biocontrol mechanisms of this species is gradually increasing (Liu et al, 2017;Martinez-Raudales et al, 2017;Dong et al, 2023;Li et al, 2023). Previous reports on the complete genome of B. velezensis mainly focused on the general characteristics of the genome and its effects on growth promotion, with less emphasis on in-depth analysis of biocontrol functions and mechanisms.…”
Section: Discussionmentioning
confidence: 99%